2015
DOI: 10.1016/j.jpsychores.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities and psychopharmacological outcomes of phantom bite syndrome

Abstract: PBS is generally not associated with severe psychiatric disorders. Absence of a dental trigger predicts a psychiatric comorbidity, which affects the psychopharmacological outcome. Antidepressant or antipsychotic therapy may be effective for symptom management in PBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 16 publications
0
57
0
2
Order By: Relevance
“…PBS is an uncommon manifestation; however, dentists are concerned mainly with the mechanical aspects of occlusion, adding further complications to PBS. In a previous study, we had reported that PBS patients with a dental trigger had significantly less psychiatric history than those without a dental trigger . Hence, the symptoms of PBS cannot be explained by a mental disorder alone.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…PBS is an uncommon manifestation; however, dentists are concerned mainly with the mechanical aspects of occlusion, adding further complications to PBS. In a previous study, we had reported that PBS patients with a dental trigger had significantly less psychiatric history than those without a dental trigger . Hence, the symptoms of PBS cannot be explained by a mental disorder alone.…”
Section: Introductionmentioning
confidence: 85%
“…All participants in this study had been diagnosed with PBS by a specialist in psychosomatic dentistry, based on the criteria suggested by Melis, as follows: (a) complaints of an uncomfortable sensation while biting; (b) significantly associated emotional distress; (c) symptoms lasting more than 6 months; (d) history of failures of various bite‐altering dental procedures; (e) absence of dental occlusion discrepancies or those disproportional to the complaint; and (f) not attributed to another disorder (dental, pathology, muscle, temporomandibular joint or neurological disorder). Our data included patients who had been analysed in one of our former studies . Exclusion criteria were the presence of a history of organic brain disorder, obvious neurological disorders in the trigeminal nerves and patients with communication difficulties.…”
Section: Methodsmentioning
confidence: 99%
“…As routine practice, oral medication [3,4] and cognitive behavioral therapy [5] are recommended for treatment of OD patients. Recently, neuromodulation therapy has been clinically recommended for treating cognitive deficits in psychiatric disorders [64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent occlusal discomfort is a common complaint among occlusal dysesthesia (OD) patients [1][2][3][4] who, in the presence of depression, schizophrenia, panic, or somatoform disorders [5][6][7][8], present with numerous neuropsychological associations. From a clinical standpoint, Tsukiyama et al [2] recommended a psychosomatic evaluation for diagnosis, and Reeves JL and Merrill RL [5], and Toyofuku et al [7] also recommended cognitive behavioral therapy and antidepressants for the treatment of OD patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a survey of patients with temporomandibular disorders (TMD), over 30% reported some bite discomfort, and about 10% reported uncomfortable bite almost all of the time . It seems to be differently distributed between the genders with higher female prevalence , similarly to the higher female prevalence of TMD that sometimes are comorbid with the disease . However, such female preponderance is not reported in all the studies .…”
Section: Epidemiologymentioning
confidence: 96%